Cognitive Style (Independence - Dependence) on the Cognitive Field of University Students (The International Journal of Educational Sciences and Arts, 2023)
the research aims to measure the cognitive style (independence - dependence) on the cognitive field of university students and identifying the significance of the difference in the cognitive style (independence - dependence) on the cognitive field of the research sample according to the gender variable (male, female) and the specialization type variable (scientific, human).  And the stage variable (second, fourth), The research sample consisted of (812) male and female students from the (second and fourth) stages of the faculties of the University of Mosul, from both disciplines (scientific and human) and of both sexes (male and female). A cognitive style test was prepared by (Wetken), and the data were processed statistically by using the statistical bag (SPSS).  Appropriate statistical methods were used, including the t-test, Pearson's correlation coefficient, and Cronbach's alpha coefficient. The following results show that University students enjoy the cognitive style, relying on the cognitive field more than independence.  There are differences between males and females in the cognitive style (independence - dependence) on the field, where males are more dependent on the field. There are differences between the second and fourth stage students in the cognitive style (independence - dependence) on the field, whereas the second stage students are more dependent on the field. There is a statistically significant difference in the cognitive style (independence - dependence) according to the specialization variable (scientific, humanistic), where the students of the humanities specialization are more dependent on the field.
Keywords: Cognitive Style; University Students; Independence; Dependence